2021
DOI: 10.1159/000521424
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Dissociation and Symptoms of Post-Traumatic Stress Disorder in Inflammatory Bowel Disease: A Case-Control Study

Abstract: Background. Several psychological disorders have been described in patients affected by Inflammatory Bowel Disease (IBD). Few studies have focused on the relationship between IBD and Post-Traumatic Stress Disorder (PTSD) symptoms, and no data are available on the relationship between IBD and dissociative symptoms. Aim of the present study was to evaluate the prevalence of PTSD and dissociative symptoms in a sample of IBD patients compared to healthy controls. A possible relationship with disease activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Charles N Bernstein et al used population-based administrative health data from Manitoba, Canada finding that the incidence rate and prevalence of mental disorders ascended in the IBD population (13). Daniele Ferrarese et al observed a high prevalence rate of PTSD and dissociative symptoms among IBD patients (14). Maunoo Lee et al reported that children with autism spectrum disorders have a higher prevalence rate of IBD using the data from the Military Health System database (15).…”
Section: Introductionmentioning
confidence: 99%
“…Charles N Bernstein et al used population-based administrative health data from Manitoba, Canada finding that the incidence rate and prevalence of mental disorders ascended in the IBD population (13). Daniele Ferrarese et al observed a high prevalence rate of PTSD and dissociative symptoms among IBD patients (14). Maunoo Lee et al reported that children with autism spectrum disorders have a higher prevalence rate of IBD using the data from the Military Health System database (15).…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 systematic review of 23 studies on the prevalence of PTS in GI conditions found approximately 36% of patients had PTS 20 . However, only a small subset of these studies assesses medical events as the cause of PTS and are limited to inflammatory bowel disease (IBD) 21–26 and GI cancers 27,28 …”
Section: Introductionmentioning
confidence: 99%
“…A 2021 systematic review of 23 studies on the prevalence of PTS in GI conditions found approximately 36% of patients had PTS. 20 However, only a small subset of these studies assesses medical events as the cause of PTS and are limited to inflammatory bowel disease (IBD) [21][22][23][24][25][26] and GI cancers. 27,28 In IBD, 90% of patients with Crohn's disease in a Swiss cohort reported some symptoms of disease-related PTS and those who had more severe symptoms were 4.3 times more likely to have IBD exacerbation.…”
Section: Introductionmentioning
confidence: 99%